Causes and effects of pole vault plant box landings and potential improvements - Johnson, J.; Boden, B. P. (Track Coach, 2017)
Plant box landings have long been a major cause of serious and catastrophic injuries to pole vaulters. With the advent of rubberized runways with underlaid concrete in the late 1960's pole vault plant boxes became extremely hard and unyielding. Our force impact data shows that a fall from only 12.5 feet is in fact three times greater than an impact capable of causing a 100% probability of a fatal head injury. The purpose of this study was to first analyze the causes of pole vault box landings and analyze the approximate fall heights and potential force impacts associated with each kind of accident. And to develop box installation strategies to remedy the problem and thus improve pole vault safety.